The Emerging Role of Long Non-coding RNAs and Circular RNAs in Coronary Artery Disease - Ghafouri-Fard, Soudeh; Gholipour, Mahdi; Taheri, Mohammad (Frontiers in Cardiovascular Medicine, 2021)
Coronary artery disease (CAD) is a common disorder caused by atherosclerotic processes in the coronary arteries. This condition is resulted from abnormal interactions between numerous cell types in the artery walls. The main participating factors in this process are accumulation of lipid deposits, endothelial cell dysfunction, macrophage induction, and changes in smooth muscle cells. Several lines of evidence underscore participation of long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) in the pathogenesis of CAD. Several lncRNAs such as H19, ANRIL, MIAT, lnc-DC, IFNG-AS1 and LEF1-AS1 have been shown to be up-regulated in the biological materials obtained from CAD patients. On the other hand, Gas5, Chast, HULC, DICER1-AS1 and MEG3 have been down-regulated in CAD patients. Meanwhile, a number of circRNAs have been demonstrated to influence function of endothelial cells or vascular smooth muscle cells, thus contributing in the pathogenesis of CAD. In the current review, we summarize the function of lncRNAs and circRNAs in the development and progression of CAD.